2014
DOI: 10.1016/j.bjid.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Entecavir therapy in elderly patients with chronic hepatitis B infection

Abstract: Chronic infection with hepatitis B virus (CHB) affects as many as 350-400 million people worldwide and 93 million people in China. 1 Moreover, elderly patients with CHB are increasing. Hence, the treatment of elderly patients with CHB is an important issue. However, to our knowledge, there is no report about the efficacy of Entecavir (ETV) treatment on elderly patients (≥60 years) with CHB.A retrospective cohort study was conducted between February 2006 and March 2008; 40 consecutive Chinese patients aged ≥60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
0
1
Order By: Relevance
“…Some studies have found longer time to and lower rate of HBV DNA negativity in the subgroups of patients with e antigen positivity and higher baseline HBV DNA level [11,13,15,17], but others have not as in our study [18,19]. Studies have also found that previous NA exposure, age more than 60 years and the presence of cirrhosis do not influence viral suppression during prolonged therapy as our study [4,13,18,20].…”
Section: Discussioncontrasting
confidence: 45%
“…Some studies have found longer time to and lower rate of HBV DNA negativity in the subgroups of patients with e antigen positivity and higher baseline HBV DNA level [11,13,15,17], but others have not as in our study [18,19]. Studies have also found that previous NA exposure, age more than 60 years and the presence of cirrhosis do not influence viral suppression during prolonged therapy as our study [4,13,18,20].…”
Section: Discussioncontrasting
confidence: 45%